Novo desenvolvimentismo e velhas condições de trabalho?: uma análise da dinâmica de subcontratação no complexo de Suape - Moraes, Aline Fábia Guerra de (2015)
The developmental policies, implemented in the Northeast by means of PAC, have Suape as its greatest expression. The indices of economic growth in that region are high, however this does not seem to reflect in a direct improvement of the people's lives. Would the new developmental policies be in fact rescuing historical social debts? In that sense, it is our task to ask how the local development is taking place, taking in consideration the work conditions of the region's workers, in special the workers employed at companies that outsource services to big companies such as the Estaleiro Atlântico Sul. Thus, this work has the goal to analyse the work conditions in the companies that provide services to the production activities of the Estaleiro Atlântico Sul, at Complexo Portuário de Suape. For this, subjects such as contracting, promotion/qualification, working hours, wage, conflict resolution, hierarchies, relation between the outsourced workers and the contractor, workplace security, etc. The choice for the Estaleiro Atlântico Sul was made as it is a company with a great expression inside Complexo de Suape, in addition to being the biggest shipyard in Latin America. The in-depth interview method was used. Four outsourced workers were interviewed. For the analysis it was also considered the testimonials of an employee of the shipyard, two union representatives, and two jurists. Thereby it was possible to conclude that the work conditions of the outsourced workers reiterate the precarious standard of the labor relations of the historical developmental policy of the country, since labor has been kept precarious in the region, relying on extensive work hours, worker cooptation in ways derived from management of the paternalist kind, low qualification, among other features of a kind of "predatory" outsourcing in the country.